2001
DOI: 10.1577/1548-8454(2001)063<0191:pabsro>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Behavioral Stress Responses of Walleyes Transported in Salt and Buffered-Salt Solutions

Abstract: To evaluate the value of transporting fingerling walleyes Stizostedion vitreum in buffered sodium chloride, we monitored blood chemistry, behavior, and water quality in conjunction with two 5-h transport trips. The control salt mixture was 0.50% sodium chloride (NaCl), and the buffered treatment was 0.45% NaCl and 0.05% sodium bicarbonate (NaHCO 3 ). We also collected posthaul blood samples from walleyes 2 h after they were placed into cages in East Okoboji Lake, as well as daily during a 72-h recovery period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 9 publications
1
23
1
Order By: Relevance
“…In general, walleyes sampled at tournaments showed greatly elevated plasma cortisol levels, especially when compared with the angled controls. It is noteworthy, however, that the cortisol levels in tournament walleye are within the same range as, or less than, those observed in walleye following other types of stresses (Barton and Zitzow 1995; Forsberg et al 2001; Barton 2002; Barton et al 2003). The plasma glucose levels of the tournament walleyes were also about double those of the resting laboratory control walleyes.…”
Section: Discussionmentioning
confidence: 64%
“…In general, walleyes sampled at tournaments showed greatly elevated plasma cortisol levels, especially when compared with the angled controls. It is noteworthy, however, that the cortisol levels in tournament walleye are within the same range as, or less than, those observed in walleye following other types of stresses (Barton and Zitzow 1995; Forsberg et al 2001; Barton 2002; Barton et al 2003). The plasma glucose levels of the tournament walleyes were also about double those of the resting laboratory control walleyes.…”
Section: Discussionmentioning
confidence: 64%
“…Several studies in freshwater fish have demonstrated decreased plasma chloride levels in animals subjected to transport (Barton et al, 2002;Forsberg et al, 2001;Mazik et al, 1991). A study with matrinxã showed that addition of marine salt (NaCl) to the water can also minimize the loss of ions during transportation (Carneiro & Urbinati, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Another factor that may have influenced survival was pond harvest and hauling stress, which have been demonstrated to cause immediate and latent mortality of stocked fish. Forsberg et al (2001) observed walleye fingerlings remained disoriented at the lake bottom near the boat ramp, after a 5 h haul, for at least 5 h after stocking. Intensively reared fish at the Rathbun hatchery required minimal handling and were stocked within one h after being loaded on the distribution truck, whereas extensively reared fish were seined, cribbed, loaded and hauled 6 h for 300 m. Hatchery personnel attempted to minimize stress, yet harvest and transportation of these fish was probably more stressful than that experienced by intensively reared fish.…”
Section: Discussionmentioning
confidence: 99%